STABILITAS EKONOMI PASAR HORAS DI TENGAH PANDEMI COVID-19: ANALISIS TERHADAP DAMPAK DAN RESPONS MASYARAKAT LOKAL - Della Ananda Adha; Muhammad Rifi Ananda; Lestari Dara Cinta Utami Ginting (Juremi: Jurnal Riset Ekonomi, 2024)
The COVID-19 pandemic has had a significant impact on Pasar Horas in Pematang Siantar, North Sumatra, as well as the surrounding communities. This research aims to explore the state of the economy in Pasar Horas during the COVID-19 pandemic and the effectiveness of assistance provided by the government to businesses in traditional markets. A qualitative approach with historical methods was used to gain an in-depth understanding of the conditions. The results show that the COVID-19 pandemic has caused a drastic decrease in income for Pasar Horas traders. The assistance provided by the government is considered inadequate by some people, while others feel that they do not need assistance because they already have enough material resources. There are also different views among the community around Pasar Horas regarding the assistance provided during the COVID-19 pandemic. Based on the results and discussion, it is recommended that the local government increase assistance to Horas Market traders who are economically affected by the COVID-19 pandemic. Horas Market traders need to innovate in selling, such as increasing online marketing. The community around Pasar Horas needs to continue to support local merchants by purchasing their products. The implementation of health protocols should also be improved in Pasar Horas to ensure the safety and health of traders and buyers during the pandemic